2001
DOI: 10.1021/la001227a
|View full text |Cite
|
Sign up to set email alerts
|

Nonionic Amphiphilic Bilayer Structures under Shear

Abstract: The effect of shear on the lamellar phase of amphiphilic systems has been widely studied in a variety of amphiphilic systems as a function of shear rate. In this investigation, we fixed the shear rate and performed temperature scan experiments on a two-component (C10E3-water) system. We observed a sequence of phases, from the low to high temperature range: multilamellar vesicle to planar lamellar to sponge phase. The shear-induced multilamellar vesicle (MLV) phase exhibited the most interesting behavior and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
111
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(119 citation statements)
references
References 36 publications
8
111
0
Order By: Relevance
“…For the present composition, d=6 nm [8,25,26]. With these values for c and d and the temperature T=298 K, we obtain b/c=14.9 Pa s 1/2 , which is approximately twice the measured value.…”
Section: Polarized Light Microscopysupporting
confidence: 54%
See 3 more Smart Citations
“…For the present composition, d=6 nm [8,25,26]. With these values for c and d and the temperature T=298 K, we obtain b/c=14.9 Pa s 1/2 , which is approximately twice the measured value.…”
Section: Polarized Light Microscopysupporting
confidence: 54%
“…The MLVs at higher surfactant concentrations are polyhedral. They fill space with a total volume fraction which is essentially unity [8,34] and N/V is approximately proportional to R )3 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As has already been shown in the C 10 E 3 system (Le et al, 2001;Oliviero et al, 2003), the fraction of onions under shear flow strongly depends on temperature. In our previous SAXS study on the C 16 E 7 system at rest, we have shown that bilayers in the lamellar phase have water-filled defects below about 341 K and that the fraction of the defects increases with decreasing temperature (Minewaki et al, 2001).…”
Section: Figuresupporting
confidence: 55%